-3x + y = 2 Equation (1)
7x -8y = 1 Equation (2)
Let us solve the system of equations with the elimination method.
-24x + 8y = 16 (Multiplying the equation 1 by 8)
+ 7x - 8y = 1 (Adding the equation 2 to the last form of the equation 1)
------------------
-17x = 17 (Adding like terms)
x = 17/(-17) ( Dividing by -17 on both sides of the equation)
x= -1
Replacing x=-1 in the equation 1,we have:
-3(-1) + y = 2
3 + y = 2 (Multiplying and using the sign rules)
y = 2- 3 (Subtracting 3 from both sides of the equation)
y = -1 (Subtracting)
The answers are x=-1 and y=-1